Dampak Limbah Industri Pengolahan Ikan Terhadap Lingkungan di Muncar, Banyuwangi, 1970-2017 - Juliansyah, Mohammad Ramdan (Lembaran Sejarah, 2023)
This paper aimed to explain the impact of industrial waste in Muncar since 1970-2017. The negative impact was related to the fishing industry that disposed their waste over the river. The research using environmental history approach to analyze this phenomenon and using newspaper, archive, magazine, and interview as the sources. The analysis showed that the impact of industrial waste in Muncar causes water pollution and air pollution. Since 2000s, the pollution had been gone worse. Uniquely, the data showed that villages inhabitants had been gained a profit from it. They were utilized the waste to be proceeded as fish oil, fish meal powder, and cattle food.